Büyük spor organizasyonlarında kullanılan güvenlik sistemleri : İstanbul maratonu örneği - Kuş, Ahmet Ayhan (My University, 2019)
Spor, ülkeleri birleştiren en büyük organizasyon faaliyetleri bütünüdür. Ancak bu organizasyonların başarılı ve etkili olmasında temel olarak seyirci ve sporcuların güvenliği ön plana çıkmaktadır. Ülkelerin sağladığı güvenlik ölçüsünde değerlendirilen faaliyet raporu güvenliğin ne derece etkin rol oynadığını göstermektedir.Sporda güvenlik; İstanbul Maratonunda OHAL öncesi ve OHAL dönemi özel ve kamu güvenlik birimleri tarafından alınan güvenlik önlemlerinin katılımcı yaklaşımı açısından analiz edilmesini esas almaktadır.Son zamanlarda, spor aktivitelerinde yaşanan güvenlik sorunları ülkenin gündemini meşgul etmektedir. OHAL döneminde ülke genelinde çıkan olaylarda yaşanması muhtemel can ve mal kayıplarının önlenmesi için alınan kamu ve özel güvenlik tedbirlerinin yeterliliği tartışılmaktadır. Bu kapsamda, İstanbul Maratonu için de en önemli problemlerinden biri güvenlik ve güvenlik uygulamalarıdır. Spor organizasyon yöneticileri, İstanbul Maraton’da düzenlendiği güzergâhlarda alınan güvenliğin; katılımcı güvenliğini, genel asayişin sağlanması, maratona giriş kontrolü, katılımcı yönlendirme, kalabalık kontrolü, sporcuların ve spor malzemelerinin korunması gibi güvenlik tedbirlerini almak için İstanbul Maraton’da kamu ve özel güvenlik birimlerine ihtiyaç duymaktadır.Önerilen bu projede: Sporda Güvenlik Sistemleri ve İstanbul Maratonun Güvenliğinin yasalar ve kanunlar çerçevesinde; kolluk gücü ve özel güvenliğin müdahale ediş şekillerinin araştırılması amaçlanmaktadır. Bu proje iki ayrı kısımdan oluşmaktadır.1.Birinci kısım sosyal bölümü spor, sporcu, maraton, katılımcı, seyirci, şiddet ve güvenlik kavramları örnekler ile vurgulanarak anlatılmıştır.2.İkinci kısım “Yasal Düzenlemeler” başlığı altında mevcut yasalarla, alınan önlemlere değinilerek, yasalarda güvenlik birimlerinin teşkilatlanması, güvenlikle ilgili birimlerin görev ve sorumlulukları oluşturmak.3.Spor organizasyonlarında kullanılan güvenlik sistemleri ile günümüzde karşılaşıla olayları ve alınan önlemleri anlatılmaya çalışılmıştır. Araştırma bölümünde ise, araştırma nicel araştırma metodolojisi içinde yer alan genel tarama modellerinden betimsel tarama modelinde gerçekleştirilmiştir. Çalışmanın sonucunda:1.Katılımcıların güvenlik algısı; yaşa, cinsiyete, medeni durum, eğitim duruma göre farklılaşmakta mıdır?2.Katılımcıların sporda güvenliğe ilişkin görüşlerinde, sporda şiddetin sorumlusunu tanımlama açısından farklılaşmakta mıdır?3.Araştırmaya katılan katılımcıların maratonda kendini güvende hissetmekte midir?4.Kamu güvenlik görevlilerinin almış olduğu güvenlik tedbirleri yeterli midir? Kamu güvenlik görevlileri güvenliğin sağlanmasında etkili midir?5.Özel güvenlik görevlilerinin almış olduğu güvenlik tedbirleri yeterli midir?6.Özel güvenlik görevlileri güvenliğin sağlanmasında etkili midir?Toplumları, hatta tüm kıtaları etkileyen spor ve spor organizasyonlarının etkin ve etkili yapılabilmesidir.İstanbul Maratonu’na katılımı artırmak için güvenli ortamlar oluşturmak ve sporda şiddeti en aza indirmek için gerekli ve gereken özen ve dikkatin yanında, yasalar ve kanunların nerelerde hangi şekilde uygulanması gerektiğini; uygulayıcı olan kolluk ve özel güvenliğin hangi koşullarda çalışmasıyla bir rol model geliştirilebileceği; ve daha sonra yapılacak çalışmalara kaynak oluşturması için hazırlanmıştır.İstanbul Maratonu’nda özel ve kamu güvenlik birimleri tarafından alınan güvenlik önlemlerinin yeterliliğinin ve etkililiğinin katılımcıların gözünden değerlendirmektir. Ayrıca çalışma sonucunda elde edilecek sonuçlardan diğer organizasyonlarda faydalanılması, çalışmanın bir geri bildirim niteliği taşıması da amaçlanmaktadır. İstanbul Maratonu’nda özel ve kamu güvenlik birimleri tarafından alınan güvenlik önlemlerinin, organizasyonun güvenliğini üstlenen İBB’nin güvenlikten sorumlu özel kolluk görevlileri, Spor İstanbul’un maratonda güvenliğini sağlayacak olan çalışanları ve çeşitli üniversitelerden gönüllü olarak güvenlik sağlamak üzere katılan öğrenciler, ki bunların tamamı spor organizasyonlarında güvenliğinde görev alan personeller olarak adlandırılacaktır. İstanbul maratonun ne kadar emin ellerde ve güvenli olup olmadığını araştırmak, ülkemizin içinde bulunduğu özel ve stratejik durumundan dolayı daha sonra düzenlenecek yarış ve organizasyonların güvenliğinde önemli bir rol oynamak ve bu organizasyonlarda güvenlik önlemlerine kaynak oluşturmak ve spor bilimlerinde yeni olan bu alana literatür açısından katkıda bulunmayı amaçlamaktadır.

Sport is the largest organization of activities that unites countries. However, the success of these organizations in the successful and effective basis of spectators and athletes is the main focus. The activity report, which is evaluated in the security measure provided by the countries, shows the extent to which security plays an effective role.Safety in sport; to analyze the security measures taken by the private and public security units in the Istanbul Marathon before and during the extraordinary eventperiod in terms of the participatory approach.Recently, security issues in sports activities occupy the country's agenda. The adequacy of public and private security measures taken to prevent possible loss of life and property in the events occurring throughout the country during the state of emergency is discussed.In this context, one of the most important problems within the Istanbul Marathon is security and security practices. Sports organization managers, Istanbul Maraton'da organized routes of security; In order to take security measures such as participant safety, general public order, marathon access control, participant orientation, crowd control, protection of athletes and sports equipment, Istanbul Maraton needs public and private security units.In this proposed project;Security Systems in Sports and Security of the Marathon in the framework of laws and laws; it is aimed to investigate the ways in which security forces and private security are interfered. This project consists of two parts. 1. The first part of the social section of sports, athletes, marathons, participants, spectators, violence and security concepts are highlighted with examples.2. The second part, under the heading of “Legal Regulations mevcut, is to establish the security units in the laws and to establish the duties and responsibilities of the security-related units with reference to the existing laws and measures taken.3. The security systems used in sports organizations and the incidents encountered today and the measures taken are tried to be explained. In the research section, the research was carried out in the descriptive survey model, one of the general survey models included in quantitative research methodology.As a result of the study;1. The security perception of the participants; Do they differ according to age, gender, marital status, educational status?2. Does the participants' views on security in sport differ in terms of defining the responsible for violence in sport?3. Do the participants in the research feel safe during the marathon?4. Are the security measures taken by the public security officers sufficient? Are public security officials effective in ensuring security?5. Are the security measures taken by the private security officers sufficient?6. Are private security officers effective in ensuring security?It is the ability to make sports and sports organizations that affect communities and even all continents effectively and effectively.It is the ability to make sports and sports organizations that affect communities and even all continents effectively and effective To develop safe environments in order to increase participation in the Istanbul Marathon and to take necessary care and attention to reduce violence to the lowest level; and to determine where and how laws and laws should be applied. It has been prepared for the future of the future with the recommendations of the law enforcement and private security under the conditions that have never been before.It is aimed to evaluate the adequacy and effectiveness of security measures taken by private and public security units in the Istanbul Marathon. In addition, it is aimed that the results of the study will be used in other organizations and the study will be a feedback feature. The security measures taken by the private and public security units in the Istanbul Marathon, the special law enforcement officers responsible for the security of the Istanbul Metropolitan Municipality, the employees who will ensure the safety of Spor İstanbul in the marathon and the students who participate in the security of the sport organizations, personnel. It is aimed to investigate how safe and secure Istanbul marathon is and to play an important role in the safety of the races and organizations which will be organized due to the special and strategic situation of our country and to contribute to this field which is new in sports sciences. .Personnel involved in the safety of the sports organizations participating in the research feel safe in marathon races?1. The personnel involved in the security of the sports organizations participating in the research are feeling safe in the marathon races.2. Does the opinions of the personnel involved in the security of sports organizations differ in terms of gender?3. Do the opinions of the personnel involved in security in sports organizations differ in terms of marital status?4. Does the opinions of the personnel involved in the security of sports organizations differ in terms of educational status?5. Do the opinions of the personnel involved in the safety of sports organizations regarding the safety in sports differ by age?6. Do the opinions of the personnel involved in the security of sports organizations about the security in sports differ in terms of frequency of attending sports organizations?7. Does the opinions of the personnel involved in the security of sports organizations differ in terms of defining the responsible of violence in sports?8. Do the opinions of the personnel involved in the security of sports organizations about the security in sports differ in terms of defining the situation of the spectators?9. Are the security measures taken in sports organizations effective for the personnel involved in the security of sports organizations?10. Are the security measures taken by public personnel taking part in the security of sports organizations sufficient?11. Are the security measures taken by the special personnel involved in the security of the sports organizations sufficient?With the help of these questions, it is possible to implement the security measures effectively in the big sports organizations that will take place in our country and to realize the impression of safer sports by the athletes and the attendees. In addition, with the contribution of this safe environment to the state with less costs and expenses to generate an income in the country's economy.
Keywords: Güvenlik sistemleri; güvenlik sistemleri sport; istanbul marathon; istanbul maratonu; marathon; Öğrenim ve öğretim; Security systems; Spor; Spor turnuvaları; Sports; Sports tournaments; Study and teaching